2024
DOI: 10.1111/jfr3.12997
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term flood exposure assessment using satellite‐based land use change detection and inundation simulation: A 30‐year case study of the Bangkok Metropolitan Region

Siriporn Darnkachatarn,
Yoshio Kajitani

Abstract: The Bangkok Metropolitan Region (BMR), located in the Chao Phraya River basin delta, is particularly vulnerable to floods, with susceptibility heightened by geographical aspects and rapid urbanization. This study aimed to assess spatiotemporal flood exposure and allow proper flood‐risk recognition among all stakeholders through a three‐phase flood exposure assessment. First, land use and land cover (LULC) changes were identified based on a 30‐year Landsat time series. Second, built‐up areas that overlapped wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…This Issue offers valuable insights into the understanding, assessment and/or management of flood risk in the urban context. Darnkachatarn and Kajitani (2024) in their research concerning the long-term flood exposure of the Bangkok Metropolitan area highlight the need and challenge of assessing flood risk in a dynamic urban context. Highlighting the critical link between urban development and increasing flood vulnerability and population exposure, their research demonstrated how urban risk in their case continued to grow irrespective of the experience of flooding.…”
mentioning
confidence: 99%
“…This Issue offers valuable insights into the understanding, assessment and/or management of flood risk in the urban context. Darnkachatarn and Kajitani (2024) in their research concerning the long-term flood exposure of the Bangkok Metropolitan area highlight the need and challenge of assessing flood risk in a dynamic urban context. Highlighting the critical link between urban development and increasing flood vulnerability and population exposure, their research demonstrated how urban risk in their case continued to grow irrespective of the experience of flooding.…”
mentioning
confidence: 99%